Delta Hemolysin and Phenol-Soluble Modulins, but Not Alpha Hemolysin or Panton-Valentine Leukocidin, Induce Mast Cell Activation - Hodille, Elisabeth; Cuerq, Charlotte; Badiou, Cédric; Bienvenu, Françoise; Steghens, Jean-Paul; Cartier, Régine; Bes, Michèle; Tristan, Anne; Plesa, Adriana; Le, Vien T. M.; Diep, Binh A.; Lina, Gérard; et al. (Frontiers in Cellular and Infection Microbiology, 2016)
Mast cells are located at host interfaces, such as the skin, and contribute to the first-line defense against pathogens by releasing soluble mediators, including those that induce itching and scratching behavior. Here, we show that delta-hemolysin (Hld) and phenol soluble modulins (PSMs) PSMα1 and PSMα3, but not alpha-hemolysin (Hla) or Panton-Valentine leukocidin (PVL), induce dose-dependent tryptase and lactate dehydrogenase (LDH) release by the HMC-1 human mast cell line. Using supernatants from isogenic strains, we verified that tryptase and LDH release was Hld- and PSMα-dependent. PSMα1 and Hld production was detected in 65% and 17% of human Staphylococcus aureus-infected skin abscess specimens, respectively, but they were produced in vitro by all clinical isolates. The results suggest that Hld and PSM-α1 produced in vivo during S. aureus skin infections induce the release of mast cell mediators responsible for itching and scratching behavior, which may enhance skin to skin transmission of S. aureus via the hands. As Hld and PSMs are upregulated by accessory gene regulator (agr), their association may contribute to the elective transmission of S. aureus strains with a functional agr system.